Deployment of Underground Wireless Sensor Network Based on Magnetic Core Antennas and Multiple Surface Acoustic Wave Sensor Modules - Kim, Sihyeok; Park, Cheolhyun; Lee, Keekeun (Journal of Electrical Engineering and Technology, 2020)
For the first time, a 3less (batteryless, chipless, wireless) underground sensor system was developed for real time monitoring of variations in temperature, humidity, and hydrogen gas concentrations around underground utility burials. The completed sensor system consists of several magnetic core antennas, surface acoustic wave (SAW) sensors, and a measurement system. Each SAW sensor was activated by pure magnetic energy, and showed high sensor performances in sensitivity and linearity. A long readout distance was observed between the upper and underground antennas, and wireless magnetic communication was analyzed in terms of the interdistances, the angles between antennas, and the underground constituent mediums. A circulator was employed to discern magnetic signals emitting and receiving in between the upper and underground systems. A COMSOL simulation and coupling of mode (COM) modeling were also conducted to determine optimal design parameters for the sensor modules, and to predict the experimental results in advance.
Keywords: Hydrogen gas concentrations; Magnetic communications; Measurement system; Optimal design parameters; Real time monitoring; Surface acoustic wave sensors; Underground systems; Underground utilities; Hydrogen sensor; Magnetic core antenna; Moisture sensor; Surface acoustic wave; Temperature sensor; Underground wireless sensor network